Telegram from Marianne and Viktor Homburger to Max Bredig - Homburger, Marianne; Homburger, Viktor (1941)
Telegram to Max Albert Bredig (1902-19770 from Marianne Homburger (1903-1986) or Viktor Homburger (1888-1968). Telegram says that passage and “accreditation” have been received.
Keywords: Homburger, Marianne, 1903-1986; Homburger, Viktor, 1888-1968; Jewish Holocaust (1939-1945); Bredig, Max Albert, 1902-1977; Telegraph; Emigration and immigration